Sensation seeking correlates with increased white matter integrity of structures associated with visuospatial processing in healthy adults - Escelsior, Andrea; Inuggi, Alberto; Amadeo, Maria Bianca; Engel-Yeger, Batya; Trabucco, Alice; Esposito, Davide; Campus, Claudio; Bovio, Anna; Comparini, Sara; Pereira da Silva, Beatriz; Serafini, Gianluca; Gori, Monica; et al. (Frontiers in Neuroscience, 2023)
The ability to process sensory information is an essential adaptive function, and hyper- or hypo-sensitive maladaptive profiles of responses to environmental stimuli generate sensory processing disorders linked to cognitive, affective, and behavioral alterations. Consequently, assessing sensory processing profiles might help research the vulnerability and resilience to mental disorders. The research on neuroradiological correlates of the sensory processing profiles is mainly limited to the young-age population or neurodevelopmental disorders. So, this study aims to examine the structural MRI correlates of sensory profiles in a sample of typically developed adults. We investigated structural cortical thickness (CT) and white matter integrity, through Diffusion Tensor Imaging (DTI), correlates of Adolescent/Adult Sensory Profile (AASP) questionnaire subscales in 57 typical developing subjects (34F; mean age: 32.7 ± 9.3). We found significant results only for the sensation seeking (STS) subscale. Positive and negative correlations emerged with FA and RD in anterior thalamic radiation, optic radiation, superior longitudinal fasciculus, corpus callosum, and the cingulum bundle. Exploring correlation between sensation seeking and whole brain cortical thickness no correlations were found. Overall, our results suggest a positive correlation between sensation seeking and higher white matter structural integrity in those tracts mainly involved in visuospatial processing but no correlation with gray matter structure. The enhanced structural integrity associated with sensation seeking may reflect a neurobiological substrate linked to active research of sensory stimuli and resilience to major psychiatric disorders like schizophrenia, bipolar disorder, and depression.